Allergic Angioedema and Urticaria After Ingestion of Organic Tea - Susanne, I. Scott MRCS; Eva, Rye Rasmussen (Journal of Dentistry And Oral Implants, 2016)
Allergic angioedema of the airways is a potentially life-threatening condition. The allergen can be difficult to identify. Treatment in the acute phase comprises of antihistamines, steroids, adrenaline and in severe cases prophylactic intubation. Allergic angioedema can be encountered in all medical specialties including odontology. It can develop fast and emergency treatment is lifesaving. Knowledge of symptoms and emergency treatment is important. We present a case of a 33-year-old female physician who in a matter of hours developed first an atypical urticarial eruption followed by angioedema of the upper airways. She was treated with antihistamines, as she refused other treatments due to lactation. The patient also refused further investigations, however she has not had any further episodes after discontinuing the ingestion of organic tea. Allergic reactions are unpredictable and have a large variety of triggers. The most likely trigger in this case was fungicide in the organic tea.
Keywords: Angioedema; anaphylaxis; allergy; tea; fungicide.